RAGAM PERMINTAAN POTENSIAL TERHADAP EKOWISATA SPIRITUAL PADA MASYARAKAT BOGOR - Pratiekto, Priyono Eka (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Spirituality is not only able to control human’s individual desire in raising and spending wealth, but it can also become a social force that significantly influence economic behaviors at community level, especially in the demand aspect and decision to consume any kind of product and service. This study was conducted toward various groups of income levels and religious backgrounds among community that resides in the district and the city of Bogor in order to gain a deeper understanding regarding the demand for eco- spiritual tourism as well as the correlation of its influencing factors. The survey showed that the income levels of Bogor community has no correlation toward their current potential demand to conduct spiritual tourism, which averaged at five visits/person/year. However, respondents' income levels are positively correlated with the value of willingness to pay a spiritual tourism trip, which indicates that the increase in income of respondents will be followed by a greater willingness to pay for doing spiritual tourism. Therefore, the findings could be useful as a source of ideas for any involved parties to transform and optimize the potential demand into actual demand and to develop eco –spiritual tourism market through customer segmentation based on income levels.Keywords: Bogor society, eco-spiritual tourism demand, willingness to pay